Analysis of the Effectiveness of Land and Building Tax Revenue on the Original Regional Income of Samarinda City in 2021-2023 - Silambi, Samrianto; Lau, Elfreda Aplonia; Sonaria, Mita (The Es Accounting And Finance, 2024)
This study seeks to assess the impact of Land and Building Tax Revenue on Original Regional Income. within the Samarinda City Regional Revenue Agency in 2024. This research is grounded in the theoretical concepts of effectiveness, contribution, Land and Building Tax, and Original Regional Income. This research methodology is quantitative. This study employs effectiveness and contribution analysis instruments. Effectiveness Formula = Realisation of Land and Building Tax: (Land and Building Tax Target) x 100%. Contribution Formula = Realised PBB Revenue: Realised PAD Revenue multiplied by 100%. The necessary data encompasses three years: 2021, 2022, and 2023. Data was acquired from the Regional Revenue Agency of East Kalimantan Province. This study demonstrates that the efficacy of land and building tax revenue in Samarinda is categorised as highly effective, with an efficacy rating of 125.07%. The impact of land and building tax on initial regional income is deemed inadequate, since it represents merely 11.08% of the entire value.